Representing the Muted Others on Social Media: Multimodal Analysis of @pelanginusantara_org’s Instagram Account - Bambang Haryono; Nikmah Suryandari; Nurul Rahmawati, Farida (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2025)
This study examined the representation of lesbian, gay, bisexual, transgender, queer, and the likes (LGBTQ+) identity in @pelanginusantara_org Instagram accounts in the midst of heteronormative dominance and marginalization of queer narratives by mainstream media in Indonesia. This study uses Muted Group Theory as the main theoretical framework to understand how queer communities construct counter-discourses against the symbolic structures that exclude them. The analysis was carried out through the multimodal analysis approach proposed by Kress & van Leeuwen, which was strengthened with the perspective of Butler’s gender performativity theory, in order to interpret visual, linguistic, and symbolic strategies in building queer identity in the digital space. The results show that this account uses strategies of visual affirmation, cultural localization, and affective narratives to challenge heteronormative discourses and create a more inclusive counter-public space. These findings confirm that social media, especially Instagram, has transformational potential for the LGBTQ+ community in Indonesia in negotiating identity and building a more equitable and humane alternative representation.